Knowledge and attitude towards cervical cancer among women in the suburban area: a cross-sectional study / Fatin Syahzani Abd Manap, Nurul Ain Adiba Mohd Rashid and Noraini Hashim - Abd Manap, Fatin Syahzani; Mohd Rashid, Nurul Ain Adiba; Hashim, Noraini (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Cervical cancer is preventable and curable in its early stage, but it remains the second leading cause of cancer-related deaths among Malaysian women. Therefore raising awareness is crucial to reducing cervical cancer incidence and mortality rates. This study aims to assess the knowledge and attitudes toward cervical cancer among women in a suburban area in Selangor. A cross- sectional study was conducted using convenience sampling, involving 359 women aged 21 to 60. Participants completed a self-administered questionnaire through a Google link. Results showed that approximately half of the participants had moderate knowledge of cervical cancer, 179 (49.9%), while 217 (60.4%) exhibited a favorable attitude toward cervical cancer. A significant positive relationship correlation was found between knowledge and attitude (p < 0.05). The findings suggest that increasing knowledge about cervical cancer can lead to more positive attitudes. Future efforts should focus on educational programs and campaigns highlighting the importance of cervical cancer screening and its symptoms to enhance awareness.